Cryptobiosis-inspired assembly of "AND" logic gate platform for potential tumor-specific drug delivery - Hu Zhou; Gang He; Yanbin Sun; Jingguo Wang; Haitao Wu; Ping Jin; Zhengbao Zha (Elsevier, 2021)
Developing tumor-specific drug delivery systems with minimized off-target cargo leakage remains an enduring challenge. In this study, inspired from the natural cryptobiosis explored by certain organisms and stimuli-responsive polyphenol‒metal coordination chemistry, doxorubicin (DOX)-conjugated gelatin nanoparticles with protective shells formed by complex of tannic acid and FeIII (DG@TA-FeIII NPs) were successfully developed as an "AND" logic gate platform for tumor-targeted DOX delivery. Moreover, benefiting from the well-reported photothermal conversion ability of TA-FeIII complex, a synergistic tumor inhibition effect was confirmed by treating 4T1 tumor-bearing mice with DG@TA-FeIII NPs and localized near-infrared (NIR) laser irradiation. As a proof of concept study, this work present a simple strategy for developing "AND" logic gate platforms by coating enzyme-degradable drug conjugates with detachable polyphenol‒metal shells.